The Multiple Functions of B Cells in Chronic HBV Infection - Cai, Ying; Yin, Wenwei (Frontiers in Immunology, 2020)
Chronic hepatitis B virus (HBV) infection is the major cause of liver damage and inflammation, of which the natural history and clinical outcomes are associated with the role of B cells. As humoral immune cells, B cells play a critical role in the process of anti-HBV antibody production. In addition, some studies have also characterized other B cell subsets involved in antigen presentation and regulating the immune response beyond antibody secretion. However, not all B cell subsets play a positive role in the immune response to chronic HBV infection and various B cell subsets jointly mediate persistent HBV infection, tolerance, and liver damage. Thus, we further elucidated the multiple functions of B cells to gain novel insight into the understanding of chronic hepatitis B (CHB) pathogenesis. We combined B cell functions with immunotherapy to explore novel therapeutic interventions for the treatment of chronic HBV infection.